The Effect of Proprioceptive Neuromuscular Facilitation and Nerve Glide Interventions on Hamstring Flexibility and Knee Extension Range of Motion in Female Recreational Runners in the Solo Runners Community - Safitri, Amaliyah Hana; I Putu Gede Adiatmika; wahyuddin (PT Inovasi Pratama Internasional, 2025)
Limited hamstring flexibility and decreased knee extension range of motion (ROM) are risk factors for musculoskeletal injuries in recreational female runners. This study aimed to compare the effectiveness of proprioceptive neuromuscular facilitation (PNF) with nerve glide in improving hamstring flexibility and knee extension ROM. This quasi-experimental pre-test–post-test study involved 20 female runners from the Solo Runners community, who were randomly assigned to two groups (PNF and nerve glide, n=10 each). Both groups underwent 12 intervention sessions over 4 weeks (3 times/week). Flexibility was measured using the Sit and Reach Test (SRT), while knee extension ROM was measured using the Active Knee Extension (AKE) test. Data were analyzed using the Wilcoxon test, paired t-test, and Mann–Whitney U test. Both interventions significantly improved hamstring flexibility (PNF Δ=+7.1 cm, p=0.004; nerve glide Δ=+5.4 cm, p=0.004) and knee extension ROM (PNF Δ=−13.2°, p<0.001; nerve glide Δ=−10.1°, p=0.005). The improvement in flexibility was greater in the PNF group than in the nerve glide group (p=0.001), whereas the between-group difference in Δ ROM was not statistically significant (p=0.057). PNF is more effective than nerve glide in improving hamstring flexibility, whereas both techniques yield similar results in improving knee extension ROM. The selection of technique should be tailored to the primary source of movement limitation, whether muscle-dominant or nerve-related.